Recurrent accident and emergency department attendance for acute asthma in children. - O'Halloran, S M (1989)
Asthmatic children aged over 5 years making repeated visits to the accident and emergency department of a children's hospital were compared prospectively, on the basis of a clinical questionnaire and pulmonary function tests, with a control group of outpatients with asthma to find the reasons for their repeated attendance. Recurrent attenders (n = 145) had more severe asthma than control subjects (n = 118), with greater airway obstruction at rest (FEV1 79% v 85% predicted) and bronchial lability (47% v 38%). Significantly more of the "emergency" group used pressurised aerosols and fewer dry powder inhalers to administer bronchodilators. There were no differences in prophylactic treatment. Seventy one per cent of parents in the emergency group had feared that their child would die during an attack, compared with 56% of control subjects. Eighty one per cent of children were self referred to the accident and emergency department. Most parents had found hospital to be the quickest means of obtaining treatment in an emergency. There were no differences between the two groups in parents' knowledge about asthma, home conditions, or social disadvantage. Although children who repeatedly attend hospital accident and emergency departments for treatment of acute attacks have more severe asthma than controls and show some deficiencies in treatment, the major determinant of attendance appeared to be the parents' conviction that appropriate treatment could not be obtained elsewhere.